2015
DOI: 10.1515/ijfe-2014-0221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Separation of Angiotensin I-Converting Enzyme Inhibitory Peptides in Chinese Soypaste

Abstract: A Chinese soypaste-derived fraction with potent angiotensin I-converting enzyme (ACE) inhibitory activity (IC 50 ¼ 25.9 μg/mL) was obtained by treating soypaste extract with 80% ethanol. The result of gradient reversedphase high-performance liquid chromatography (RP-HPLC) suggested that bioactive peptides bearing some polarity groups made a substantial contribution to the ACE inhibitory activity. By mass spectrometric analysis, a component was separated as Glu-Ser-Gly-Asp which was then found to act in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The LAM method with the 3HB-GGG substrate using the ACE kit-WST can also be applied using microplate ELISA reader. [ 48 49 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…The LAM method with the 3HB-GGG substrate using the ACE kit-WST can also be applied using microplate ELISA reader. [ 48 49 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that both PKH3 and PKH4 could bind to ACE non-active sites as well as to the enzymesubstrate complex (Asoodeh et al, 2014). Similarly, peptides from Chinese soy paste (Li et al, 2015) and flaxseed protein peptides (Udenigwe et al, 2009) were non-competitive ACE inhibitors. Moreover, competitive type (Setayesh-Mehr & Asoodeh, 2017) and mixed-type (Wang et al, 2018) of ACE inhibitory mechanisms have been reported as well.…”
Section: Pkhs Inhibit Ace In a Non-competitive Waymentioning
confidence: 92%